Sejarah Perubahan Genre Dan Tujuan Bermusik Religi Di Indonesia: Sebuah Tinjauan Sejarah-Budaya - Fikri Surya Pratama; Annisa Annisa (Tamaddun: Jurnal Kebudayaan dan Sastra Islam, 2023)
The arts, such as music, are one of the channels for the spread of Islam in the archipelago. In its development, human culture will continue to evolve, including music. From the time of Islamisation, through the colonial era to the modern era, religious music in Indonesia will undergo changes. This paper aims to explain the development of the genre and purpose of Islamic music in Indonesia. The research method used is the historical research method with its stages: 1) heuristics, research data sources are collected through literature studies; 2) source criticism, selecting the validity of research data sources; 3) interpretation with the cultural evolution theory approach; 4) historiography. The results showed that the development of classical Indonesian Islamic music was born according to the socio-cultural aspects of each region. In Java, Islamic music was born from the acculturation of Javanese culture and Islamic content. In Minangkabau, the Middle Eastern music culture (gambus & gamad) dominates instrumentally. However, the lyrical content remains on Islamic & Minangkabau themes. In later developments, Indonesian Islamic music began to be influenced by Western cultural genres and instruments. The changes are not only 'physical', but also in the purpose of contemporary Islamic music. Music that was once intended as a medium for da'wah and local Islamic cultural identity has slowly turned into 'market' oriented work or consumerism. Muslims who have become the majority have also had an influence in shifting music away from its original purpose of da'wah.